The effect of recovery strategies on physical performance and cumulative fatigue in competitive basketball - Montgomery, P. G.; Pyne, D. B.; Hopkins, W. G.; Dorman, J. C.; Cook, K.; Minahan, C. L. (Journal of Sports Sciences, 2008)
To evaluate the effectiveness of recovery strategies on physical performance during a 3-day tournament style basketball competition, 29 male players (mean age 19.1 years, s = 2.1; height 1.84 m, s = 0.34; body mass 88.5 kg, s = 14.7) were assigned to one of three treatment groups: carbohydrate + stretching (7.7 g · kg -1 · day -1, s = 1.7; 'n = 9), cold water immersion (11°C, 5 1; n = 10) or full leg compression garments (18 mmHg, ~18 h; n = 10). Effects of the recovery strategies on pre-post tournament performance tests were expressed as the mean change (% ± standard deviation of the change score). Changes and differences were standardized for accumulated game time, assessed against the smallest worthwhile change for each test, and reported qualitatively. Accumulated fatigue was evident over the tournament with small to moderate impairments in performance tests. Sprint and agility performance decreased by 0.7% (s = 1.3) and 2.0% (s = 1.9) respectively. Vertical jump decreased substantially after the first day for all treatments, and remained suppressed post-tournament. Cold water immersion was substantially better in maintaining 20-m acceleration with only a 0.5% (s = 1.4) reduction in 20-m time after 3 days compared with a 3.2% (s = 1.6) reduction for compression. Cold water immersion (-1.4%, s = 1.7) and compression (-1.5%, s = 1.7) showed similar substantial benefits in maintaining line-drill performance over the tournament, whereas carbohydrate + stretching elicited a 0.4% (s = 1.8) reduction. Sit-and-reach flexibility decreased for all groups, although cold water immersion resulted in the smallest reduction in flexibility. Basketball tournament play elicited small to moderate impairments in physical test performance. In conclusion, cold water immersion appears to promote better restoration of physical performance measures than carbohydrate + stretching routines and compression garments.